Bhutan, problems and policies - Misra, H. N. (Harikesh N.), 1945- (New Delhi, India : Heritage Publishers, 1988)
Assessment of housing, land, and settlement policies.
Includes index.
Bibliography: p. [141]-143.
Keywords: Bhutan -- Economic conditions; Bhutan -- Social policy